Sport science and medicine in tennis - Pluim, B. M.; Miller, S.; Dines, D.; Renström, P.; Windler, G.; Norris, B.; Stroia, K. A.; Donaldson, A.; Martin, K. (British Journal of Sports Medicine, 2007)
Tennis is one of the major global sports, with over 75 million participants worldwide. Many more follow the Grand Slams, Davis Cup and Fed Cup events, overseen by the International Tennis Federation (ITF) and the professional tours, governed and managed by the Association of Tennis Professionals (ATP) and the Sony Ericsson WTA (Women`s Tennis Association) Tour.